Patient Satisfaction and Complaints Handling in Health Services Quality Improvement Effort at Sijunjung Public Hospital in West Sumatra, Indonesia - Isniati; Rizanda Machmud; Nusyirwan Effendi; Rima Semiarty (Indian Journal of Forensic Medicine & Toxicology, 2021)
Complaint handling is one of the many strategies for improving health services. It is recognized that patients’ satisfaction is an indicator of the quality of care. A survey on public services revealed that public satisfaction at Sijunjung Hospital was 43.78% in the year 2015 but decreased to 40.18% in 2016. This decrease in public satisfaction is due to patients’ complaints. From 2015 to 2016 there were 198,739 complaints while from 2016 to 2017 the number increased to 208,415. The purpose of this study is to determine the factors of patient’s dissatisfaction with health care services and complaint handling to improve health services quality at Sijunjung Public Hospital. This study uses the mixed method. The initial phase of this research is done by quantitative approach using a cross-sectional design in the form of data collection and analysis. The study involves a qualitative approach using observation method, in-depth interviews, Focus Group Discussions. The study reveals that only half of the inpatients, outpatients, and Emergency Unit patients get excellent health services at Sijunjung Public Hospital. The results of the study suggest that satisfaction of patients requires an individual analysis of the patient’s needs; implementation in the health care system of functions that meet these needs.